Suspicious Financial Activity in the Context of In-Game Asset Exchange Marketplace - Emil Eminov; Stephen V. Flowerday (Journal of Cybersecurity and Privacy)
In this study, we investigated the expanding problem of suspicious activity when using online in-game asset trading platforms. The decentralized structures and anonymity offered by these platforms provide a basis for suspicious actions, creating a threat to the virtual economy. By evaluating 18,157 rows of anonymized transaction data from 38 unique sellers with the help of the interquartile range approach and network analysis, we were able to identify suspicious activities. The results highlight suspicious online activities of individual transactions. This research contributes by identifying new, concerning trends and unraveling complex networks by analyzing in-game asset transaction data. It also assists in informing experts and lawmakers about new suspicious activities.